1997
DOI: 10.1007/s004290050075
|View full text |Cite
|
Sign up to set email alerts
|

Platelets and inflammation

Abstract: Besides their functions in the haemostatic process and in thrombus formation after an endothelial injury, blood platelets also take part in the processes of inflammation and tissue repair that follows. For this purpose, they closely collaborate with all types of leukocytes. Activated platelets secret chemotactic substances, they facilitate the binding of leukocytes to the endothelium and their subsequent extravasation, and they may influence the inflammatory responses of leukocytes in both stimulating and inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
121
0
15

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(139 citation statements)
references
References 91 publications
3
121
0
15
Order By: Relevance
“…An alternate source for many of these, or similar mediators is the platelet. Platelets are anucleate cellular fragments containing ␣ granules and dense granules that, upon stimulation, can release a variety of mediators capable of inducing vascular permeability and leukocyte recruitment (37). In this study, we demonstrated that the allergeninduced, mast cell-independent increase in vascular permeability could be abrograted by the depletion of circulating platelets (Ͼ99%), confirming that this cell fragment is an important pool for a mediator of vascular permeability.…”
Section: Discussionsupporting
confidence: 61%
“…An alternate source for many of these, or similar mediators is the platelet. Platelets are anucleate cellular fragments containing ␣ granules and dense granules that, upon stimulation, can release a variety of mediators capable of inducing vascular permeability and leukocyte recruitment (37). In this study, we demonstrated that the allergeninduced, mast cell-independent increase in vascular permeability could be abrograted by the depletion of circulating platelets (Ͼ99%), confirming that this cell fragment is an important pool for a mediator of vascular permeability.…”
Section: Discussionsupporting
confidence: 61%
“…These interactions potentially induce platelet activation. Normally, non-activated platelets store CD62P in the alpha-granule membranes, but several stimulators rapidly translocate to the platelet surface (30)(31)(32)(33). Platelet activated by these stimulators releases alpha-granule constituents, such as PF4 and growth factors (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…This is a novel observation, considering that platelets have been long considered the major source of plasma sCD40L (40,50). This reversal in the predominant source of sCD40L is likely to be explained by the fact that platelets contain only preformed CD40L and lack synthetic capacity even after stimulation, whereas activated T cells can produce massive quantities of inflammatory molecules for prolonged periods of time (51). When infliximab was added to activated T cells, levels of sCD40L were significantly reduced, while platelet-derived sCD40L remained unchanged.…”
Section: Discussionmentioning
confidence: 99%